THE INFULENCE OF ELECTORAL PROGRAM OF VOLLEYBALL AND BASKETBALL ON THE TRANSFORMATION BIOMOTORICALY ABILITY OF STUDENTS - Vidran Kljajević (Sport Mont, 2013)
The research was conducted among 126 students of the third year of high school, who at the beginning of the study were 17 years old ± 6 months.Sample is divided into experimental (E) group, which had 51 respondents, and the control group (K) in where there were 76 respondents.With the experimental group participants realized voleyball elective program in the first half and the electoral program of basketball in the second half. A control group of subjects practiced by'' standard'' teaching program that included content from athletics, gymnastics, dance and sports games. In this paper, we will make reference to our results obtained in the space biomotoricaly abilities.